2013
DOI: 10.1007/s13197-013-0928-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of an exopolysaccharide from a probiotic Lactobacillus plantarum MTCC 9510 and its efficacy to improve the texture of starchy food

Abstract: The weight average molecular weight (Mw), number average molecular weight (Mn) and size average molecular weight (Mz) of an exopolysaccharide from probiotic Lactobacillus plantarum MTCC 9510 was found to be 2.68×10 5 Da, 2.55×10 5 Da and 2.83×10 5 Da, respectively by Gel permeation Chromatography employing the third order polynomial model. The polydispersity index (Mw/Mn) of the polysaccharide was obtained as 1.05. The exopolysaccharide and the starch-exopolysaccharide hydrocolloid exhibited a non-Newtonian an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 26 publications
(28 reference statements)
0
16
0
1
Order By: Relevance
“…). Furthermore, this strain produces an exopolysaccharide (Ismail and Nampoothiri ), which is well characterized (Ismail and Nampoothiri ) and exhibits anticancer property (Ismail and Nampoothiri ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…). Furthermore, this strain produces an exopolysaccharide (Ismail and Nampoothiri ), which is well characterized (Ismail and Nampoothiri ) and exhibits anticancer property (Ismail and Nampoothiri ).…”
Section: Introductionmentioning
confidence: 99%
“…The rational for selecting L. plantarum MTCC 9510 for this study is due to its probiotic attributes which are well established (Aswathy et al 2008). Furthermore, this strain produces an exopolysaccharide (Ismail and Nampoothiri 2010), which is well characterized (Ismail and Nampoothiri 2013) and exhibits anticancer property (Ismail and Nampoothiri 2014).…”
mentioning
confidence: 99%
“…After the broth was centrifuged at 10,000×g for 30 min, a certain volume of supernatant was taken to dialysis through 10 kDa membrane against distilled water at 4 o C for 72 h with 2-4 changes per day. EPS production of the strain was determined by phenolsulphuric acid method (11) until no single sugar was detected in distilled water.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of Ismail and Nampoothiri [11], the initial cell density of 10 9 CFU/mL was the best condition for L.plantarum MTCC 9510 to synthesize EPS. In our study, the appropriate initial cell density was at 10 6 CFU/mL.…”
Section: Effect Of Initial Cell Density On Eps Production Of L Plantmentioning
confidence: 96%
“…Li Zhang et al [1] found that L. plantarum C88 was able to produce 69 mg/L EPS in MRS medium supplemented with 2 % glucose. In other study, lactose was chosen to investigate the EPS production of L. plantarum MTCC 9510 [11].…”
Section: Effect Of Carbon Source On Eps Production Of Lplantarumt10mentioning
confidence: 99%